Role of B Type Natriuretic Peptide in the Early Diagnosis of Left Ventricular Diastolic Dysfunction in High Risk Subjects (Cardiovascular Journal, 2010)
Background: Brain natriuretic peptide (BNP) reflects left ventricular pressure. It increases in systolic dysfunction. Our aim was to evaluate role of plasma BNP level in early diagnosis of left ventricular isolated diastolic dysfunction. Methods: We studied 60 patients (male=18, female=42) with hypertension, diabetes mellitus, ischemic heart disease, dyslipidemia. The Doppler parameters used for evaluation of diastolic dysfunction are: isovolumetric relaxation time (IVRT), Transmitral flow velocities (E/A) ratio, deceleration time (DT) & pulmonary vein Doppler findings. 49 patients (group-1) had diastolic dysfunction whereas 11 patients (group-2) had normal flow patterns. Plasma BNP level was done in all patients. Results: Mean plasma BNP levels were 40.41±6.82 pg/ml in individuals with normal filling patterns and 183.36±25.28 pg/ml in subjects with abnormal diastolic dysfunction (p